In vivo zebrafish assays for analyzing drug toxicity. (May 2014) - Raldúa, Demetrio; Piña, Benjamin
<x xml:space="preserve">Abstract</x> Introduction: Off-target effects represent one of the major concerns in the development of new pharmaceuticals, requiring large-scale animal toxicity testing. Faster, cheaper and more reliable assays based on zebrafish embryos (ZE) are being developed as major tools for assessing toxicity of chemicals during the drug-discovery process. Areas covered: This paper reviews techniques aimed to the analysis of in vivo sublethal toxic effects of drugs on major physiological functions, including the cardiovascular, nervous, neuromuscular, gastrointestinal and thyroid systems among others. Particular emphasis is placed on high-throughput screening techniques (HTS), including robotics, imaging technologies and image-analysis software. Expert opinion: The analysis of off-target effects of candidate drugs requires systemic analyses, as they often involve the complete organism rather than specific, tissue- or cell-specific targets. The unique physical and physiological characteristics of ZE make this system an essential tool for drug discovery and toxicity assessment. Different HTS methodologies applicable to ZE allow the screening of large numbers of different chemicals for many diverse and relevant toxic endpoints.